Assessment of dynamic thiol-disulfide homeostasis in patients with lipoid proteinosis (Urbach-Wiethe syndrome) - Taskin,Seyhan (2022)
SUMMARY OBJECTIVE: Lipoid proteinosis is a rare autosomal recessive genetic dermatological disease that occurs due to the accumulation of hyaline material in the skin and mucous membranes. This study aimed to investigate whether dynamic thiol-disulfide homeostasis is a new marker of oxidative stress in patients suffering from lipoid proteinosis. METHODS: The study group involved 17 patients with lipoid proteinosis and 17 healthy controls with same gender and age. Native thiol, total thiol, disulfide levels, and thiol-disulfide indexes were measured with the fully automated spectrophotometric method described by Erel and Neselioglu, and the results of the two groups were statistically analyzed. RESULTS: Serum total thiol and native thiol levels were significantly lower in lipoid proteinosis group compared to the control group (p=0.020 and p=0.014, respectively). The disulfide levels were found to be higher in lipoid proteinosis group, but there was no significant difference between two groups. CONCLUSIONS: Impaired dynamic thiol-disulfide homeostasis was observed in lipoid proteinosis patients, suggesting that thiol-disulfide homeostasis may have a role in the pathogenesis of this disease.